Clinical and Pathological Study of Tumor Border Invasion—Is Narrow Resection Margin Acceptable in Hepatoblastoma Surgery? - Shen, Gang; Wu, Linlin; Zhao, Jie; Wei, Bin; Zhou, Xianjun; Wang, Feifei; Liu, Jie; Dong, Qian (Frontiers in Medicine, 2020)
Aim: To study clinically and pathologically whether narrow resection margin (< 1cm) is acceptable in hepatoblastoma surgery. Methods: A total of 42 patients who underwent surgery for hepatoblastoma were selected, and these patients were divided into 2 groups according to whether or not preoperative chemotherapy(CHT). The general characteristics of the patients were summarized, the resection margin distance were recorded, the event-free survival rates were followed up. Pathologically, HE staining and immunochemical staining were used to study the invasion distance outside the tumor capsule in tumor border. Results: Clinically, the event-free survival rates were not significantly different between the patients with wide resection margin (>1cm) and narrow resection margin (<1cm) of the two groups. Pathologically, the tumor of all 42 patients had capsules surrounding the tumor. Of the patients in Group 1 (without preoperative CHT), 9% (2/22) had micro-metastatic cancer nests outside the capsule, and the farthest distance from the cancer nests to the capsule was 4.6mm. Of the patients in Group 2 (with preoperative CHT), 75% (15/20) showed residual cancer nests in the paratumor liver tissue, and the farthest distance was 9.6mm; 3 and 2 cases respectively showed extracapsular intravascular microtumorous thrombi. Conclusion: Clinically and Pathologically, narrow resection margin is acceptable in hepatoblastoma surgery.